2015
DOI: 10.1177/0263774x15614144
|View full text |Cite
|
Sign up to set email alerts
|

Does market concentration affect prices in the urban water industry?

Abstract: Abstract. This paper analyzes the relationship between market concentration in the private segment of the water industry and water prices with a sample of municipalities located in the Southern Spanish region of Andalusia. In doing so, several Heckman sample selection models are estimated with the main finding being that market concentration increases the price of water for residential use charged by private companies. The main policy recommendation is that urban water service privatization must be accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The differences in the cost of water resource abstraction, purification techniques of raw water, the distance to the place of water supply, or the type of wastewater treatment may explain the differences in prices charged to the user. However, there is also evidence that differences in water prices in Spain can be explained in part by the ideology of the political party in the local government [34,36], the type of management (public or private) [25,26], and the level of market concentration in the industry [28].…”
Section: Social Concerns: Affordability Fairness and Equitymentioning
confidence: 99%
“…The differences in the cost of water resource abstraction, purification techniques of raw water, the distance to the place of water supply, or the type of wastewater treatment may explain the differences in prices charged to the user. However, there is also evidence that differences in water prices in Spain can be explained in part by the ideology of the political party in the local government [34,36], the type of management (public or private) [25,26], and the level of market concentration in the industry [28].…”
Section: Social Concerns: Affordability Fairness and Equitymentioning
confidence: 99%
“…On the one hand, some previous studies have detected higher price levels under private provision (Martínez-Espiñeira et al 2009). Similarly, Bel et al (2015) found that private firms with a larger market share set higher water prices. On the other hand, some studies conclude that public management does not necessarily lead to lower prices.…”
Section: Spainmentioning
confidence: 89%
“…Moreover, Spanish water industry is highly concentrated. Aqualia and Aguas de Barcelona are the two main private operators 9 (García-Valiñas et al 2013;González-Gómez et al 2014;Bel et al 2015).…”
Section: Ppps In Spanish Water Sector: Schemes and Figuresmentioning
confidence: 99%
“…Finally, empirical research on another type of service, public water, has delved further into this issue. According to Bel et al (2015), public corporations with private participation in the Spanish water industry are characterized by relatively high service prices, in comparison to classic externalization initiatives. They argue that when local governments exert more direct control over service management in institutional public-private partnerships, it becomes more difficult to determine the quantity and quality of water services, leading to higher costs and ultimately higher prices for the consumer.…”
Section: Public and Private: Purely Public And Mixed Firmsmentioning
confidence: 99%